Economic Decision-Making Tool for Distributed Solar Photovoltaic Panels and Storage: The Case of Chile - Chavez-Orostica, H; Vasquez-Perez, O; Villalobos-Cid, M; Rojo-Gonzalez, L; Troncoso-Martinez, N (Elsevier Ltd, 2019)
The benefits of distributed solar photovoltaic (PV) panels and storage have been widely reported in the literature. However, the economic impact on the electricity bill due to its implementation is generally unknown by the distribution customers. In this work, we develop an economic decision-making tool for the case of Chile. This tool is based on an easy-to-implement algorithm, which computes the number of solar PV panels and batteries that maximize the economic return in a given time horizon subject to several technical constraints. To illustrative the usefulness of our tool, a personal computer implementation and a numerical example are considered. The obtained results compute the economic benefit in net present value of the best alternative solar PV panels and batteries in an execution time less than 30 seconds. © 2019 The Authors. Published by Elsevier Ltd.